THE THICKNESS OF THE LAYER PATTERN ON THE METHOD OF LOST FOAM CASTING AGAINST THE ACCURACY OF THE SIZE OF THE IRON - Hasyim, Muhammad (Department of Electrical Engineering, University of Patria Artha, 2018)
Lost foam casting is one of the casting method using expanded polystyrene (EPS) as an ingredient for the manufacture of patterns and planted in silica sand. When the molten metal is inserted into the mold, the EPS will melt and evaporate so that the place will be filled by a liquid metal. The purpose of this research is to know the influence of layer thickness on expanded polystyrene patterns against the accuracy of the size of the nodular cast iron 450 DISCS by using the method of lost foam casting. EPS patterns being used has a thickness 3-24 mm. Material used is upholstery material rekraktori Zircon (ZrO2) and Colloidal Silica binding materials (O2Si). The thickness of the coating material is applied to the EPS pattern i.e. 0-1300 microns. EPS patterns grown in silica sand is then compacted by means of vibration. Metal alloys smelted 450 DISCS in crucible furnace and poured into a mold at a temperature of about 1350-1450 oC oC. The average accuracy of the size for each of the thick layer of the pattern 0 (without coating), 200, 500 and 1300 Micron in a row is-0.05, 0.07 0.04,-, and-0.13. A thick layer of 200 Micron provides the best measure of the accuracy of the values of the three variations of the thickness of the layer pattern. A thick layer of 0 (without coating), 500 and 1300 Micron will result in decreased accuracy measure. Patterns that are not coated will give bad impact towards the results of castings.